Strength reduction factor evaluation of the circular reinforced concrete column with varying eccentricity ratio (e/h) - Wahyuniarsih Sutrisno; Mudji Irmawan; Dwi Prasetya (Journal of Civil Engineering, 2020)
This paper presents strength reduction factor evaluation of circular reinforced concrete column with varyingeccentricity ratio (e/h) using the first-order-reliability-methods. The resistance properties of the reinforced concrete column isestimated using the monte-carlo simulation with random normally distributed material properties. Only dead and live loadcombination considered in the analysis. The parameters being investigated when evaluating the resistance of the reinforcedconcrete column are the concrete compressive strength, steel yield strength, coefficient of variation for both the concrete andsteel materials, reinforced concrete column size, and the longitudinal reinforcement ratio. When evaluating the strengthreduction factor, the safety index values are 3.0, 3.5, and 4.0. From the analysis, it was found out that the strength reductionfactor, for e/h higher than one and with safety index equal to 3.0, was equal to 0.9 which agrees well with the ACI 318 strengthreduction factor for tension-controlled region. However, for e/h lower than one and safety index equal to 3.0, the strengthreduction factor was equal to 0.6 which was lower than the ACI 318 strength reduction factor for compression-compressioncontrolled region.